O polskich przymiotnikach określających człowieka lubiącego pracować .......... 399 - Jaros, Irena (Gwara i kultura w słowie zapisane: Księga jubileuszowa dedykowana Profesorowi Józefowi Kąsiowi, 2025)
ON POLISH ADJECTIVES DESCRIBING A PERSON WHO LIKES TO WORK The article presents the semantic, word-formation and geographical diversity of adjectives in Polish dialects that describe people who like to work. These adjectives are suffixal derivatives formed from the verb pracować [‘to work’], i.e.: pracowity, pracowaty, pracowany, pracowny, pracowliwy [‘hard-working’], and from the nouns: praca, robota [‘work’]: pracny, robotny(ni), robocy, robotliwy, roboczuszczy [‘hard-working’]. The analysis shows that the words pracowity and robotny, which align with geneal Polish, are also common in Polish dialects.